Neonatal Ultrasound for Anorectal Malformations in Male Newborns Without Perineal Fistula: A Good Diagnostic Tool for A Safe One-Staged Surgery - Giné, Carlos; Coma, Ana; García, Laura; Laín, Ana; Barber, Ignasi; Maluje, Rodrigo; López, Manuel (Archives of Clinical and Medical Case Reports, 2021)
Background/Purpose: The standard neonatal approach for a male newborn with an anorectal malformation (ARM) and no perineal fistula remains the opening of a diverting colostomy. Here we describe radiological improvements in neonatal ultrasound (US) that characterize the recto-urinary fistula and allow a direct anorectal reconstruction. Material and Methods: This is a descriptive report of radiological findings in neonatal ultrasound in all newborn male patients with an ARM, no perineal fistula and no colostomy, recruited over a 6-year period. A paediatric radiologist actively looked for recto-urinary fistulas and their relation to anatomical landmarks. These findings, along with the clinical status and associated anomalies, were considered to indicate a single-staged procedure. Results: From 28 neonates with ARM only three met the inclusion criteria. The first 2 cases showed a bulbar and prostatic fistula in US but with associated malformations and benefited from a colostomy. The third baby presented a bulbar fistula in the US, normal sacrum and no lifethreatening malformations and benefited from a singlestaged procedure. Conclusions: Neonatal perineal US can give the same anatomical information than the distal colostogram and leads to a safe single-staged procedure in expert teams, if there is a lack of associated life-threatening malformations.